PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATERI SISTEM EKSKRESI MANUSIA KELAS XI UNTUK SEKOLAH MENENGAH ATAS - Hayati, Khusnul; nerita, siska; Fitriani, Vivi (Pendidikan Biologi, 2014)
ABSTRACTÂ Â To reach the goal of learning, teaching media is really crucial in theaching and learning process.The type of teaching media developed is interactive teaching media. It is a kind of multimedia format that is designed in compact disc with the purpose of interactive application in it. Teaching media that is commonly used at school nowadays is powe point. This kind of media still cannot attract students attention yet. Because of this problem, interative teaching media was developed for learning material excretion system at the seccondgrade of senior high school. The purpose of the study was to investigate the validity and practicality of interactive teaching media. This study was research development that used 4D Â Models consists of four stages: define, design, develop and disseminate. The research was done at develop stage. Meanwhile, at define stage, the curriculum and studentâs analysis was done. The interactive teaching media for learning material excretion system for students it self was designed at stage design. Then, the validity test was conducted at the testing. The practicality was done by two teacher and twenty students of third grade in senior high school. The data was analyzed by percentage technique and presented descriptively. The result of validity test for interactive teaching media reveals that interactive teaching media is valid, 88,65 % based on material aspect, type of media, motivation and language. Moreover, from practicality test, it shows that interactive teaching media is very practical in use, 88,64 % and the results of practicality test from students is 80,9 % (practical). Based on the result of the study, it can be concluded that interactive teaching media for learning material excretion system at the second grade of senior high school have fulfilled the validity and practicality criteria.Â